Sacrificial practices and environmental suffering: The case of the women of Tierra Amarilla, Chile - Duarte Hidalgo, Cory (2025)
The study seeks to identify the sacrificial practices present in the subjectivities and corporealities of women in the commune of Tierra Amarilla, Atacama region, Chile. The commune is a sacrificial zone marked by the high presence of extractive mining companies. The notion of sacrifice, worked theoretically from different authors, gives rise to the analysis of the sacrificial practices to which women resort to face the effects of sacrifice in their lives daily. In this way, qualitative research is proposed, with a narrative and exploratory approach, carried out through a case study. Based on semi-structured narrative interviews, we inquired into the sacrificial practices developed by the participants of the study. The sample consisted of women, participants of social groups and organizations. The results revealed a series of sacrificial practices, in addition to the habituation and normalization of environmental sacrifice, as well as possibilities of resistance.